PENGARUH MOTIVASI KERJA DAN KEMAMPUAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BANK SULUTGO - Aditya Gunawan Subakir; Efendy Rasjid; Iyam L Dua (Jurusan Administrasi Bisnis Politeknik Negeri Manado, 2022)
In the era of the industrial revolution 4.0 it becomes a challenge for every company to compete with each other to show quality companies. The purpose of this study is to find out the Effect of Work Motivation and Work Ability on Employee Performance on PT. Bank SulutGo. This type of research is quantitative research and research methods using descriptive research methods. The study took samples from one population using questionnaires as a data collection tool. The population taken is an Employee of PT. Bank SulutGo. The employees in question amounted to 427 employees but the sample involved amounted to 33 respondents using non probability sampling methods. The analysis used is Descriptive Statistical Analysis, Total Score, Multiple Linear Regression Analysis and Correlation. The results of the study's analysis The value of the simultaneous correlation coefficient r = 0.836 showed that work motivation and work ability had a very strong and significant relationship to improved employee performance at PT. Bank SulutGo. The coefficient of determination indicates that the improvement in employee performance, 83.6% is influenced by work motivation and ability to work together, while the remaining 16.4% is influenced by other factors. The results of the analysis showed that Work Motivation and Work Ability have a significant influence on improving Employee Performance in PT. Bank SulutGo. For this reason, work motivation and work ability need to be considered by the leadership and the company by paying more attention to internal and organizational factors regarding work motivation and work ability so as to improve employee performance.